Research on the Performance of Diamond-Like Carbon Coatings on Cutting Aluminum Alloy: Cutting Experiments and First-Principles Calculations - Biao Huang (Coatings, 2021)
The purpose of this study is to investigate the cutting performance of amorphous carbon (a-C) coatings and hydrogenated amorphous carbon (a-C:H) coatings on machining 2A50 aluminum alloy. First-principles molecular dynamics simulation was applied to investigate the effect of hydrogen on the interaction between coatings and workpiece. The cross-section topography and internal structure of a-C and a-C:H films were characterized by field emission scanning electron microscopy and Raman spectroscopy. The surface roughness of the deposited films and processed workpiece were measured using a white light interferometer. The results show that the a-C-coated tool had the highest service life of 121 m and the best workpiece surface quality (Sq parameter of 0.23 μm) while the workpiece surface roughness Sq parameter was 0.35 and 0.52 μm when machined by the a-C:H-coated and the uncoated tool, respectively. Meanwhile, the build-up edge was observed on the a-C:H-coated tool and a layer of aluminum alloy was observed to have adhered to the surface of the uncoated tool at its stable stage. An interface model that examined the interactions between H-terminated diamond (111)/Al(111) surfaces revealed that H atoms would move laterally with the action of cutting heat (549 K) and increase the interaction between a-C:H and Al surfaces; therefore, Al was prone to adhere to the a-C:H-coated tool surface. The a-C coating shows better performance on cutting aluminum alloy than the a-C:H coating.